The lncRNA CASC2 Modulates Hepatocellular Carcinoma Cell Sensitivity and Resistance to TRAIL Through Apoptotic and Non-Apoptotic Signaling - Sun, Jichun; Xu, Hongbo; Lei, Zhao; Li, Zhiqiang; Zhu, Hongwei; Deng, Zhen; Yu, Xiao; Jin, Xiaoxin; Yang, Zhi (Frontiers in Oncology, 2022)
The immune cytokine tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been widely concerned as a tumor therapy because of its ability of selective triggering cancer cell apoptosis; nevertheless, hepatocellular carcinoma (HCC) exhibits acquired resistance to TRAIL-induced apoptosis. In the present study, tumor-suppressive lncRNA cancer susceptibility candidate 2 (CASC2) was downregulated in HCC tissues and cell lines; HCC patients with lower CASC2 expression predicted a shorter overall survival rate. In vitro, CASC2 overexpression dramatically repressed HCC cell proliferation and inhibited cell apoptosis; in vivo, CASC2 overexpression inhibited subcutaneous xenotransplant tumor growth. CASC2 affected the caspase cascades and NF-κB signaling in TRAIL-sensitive [Huh-7 (S) and HCCLM3 (S)] or TRAIL-resistant cell lines [Huh-7 (R) and HCCLM3 (R)] in different ways. In Huh-7 (S) and HCCLM3 (S) cells, CASC2 affected cell apoptosis through the miR-24/caspase-8 and miR-221/caspase-3 axes and the caspase cascades. miR-18a directly targeted CASC2 and RIPK1. In Huh-7 (R) and HCCLM3 (R) cells, CASC2 affected cell proliferation through the miR-18a/RIPK1 axis and the NF-κB signaling. RELA bound to CASC2 promoter region and inhibited CASC2 transcription. In conclusion, CASC2 affects cell growth mainly via the miR-24/caspase-8 and miR-221/caspase-3 axes in TRAIL-sensitive HCC cells; while in TRAIL-resistant HCC cells, CASC2 affects cell growth mainly via miR-18a/RIPK1 axis and the NF-κB signaling. These outcomes foreboded that CASC2 could be a novel therapeutic target for further study of HCC-related diseases.